The Effect of Academic Model Supervision on the Workload and Stress of Nurses in Hospitals: A Literature Review - Sandra Helvitia Bulu; Regina Vidya Trias Novita (Al Makki Publisher, 2024)
Nurses often face high workloads and significant levels of stress due to the demands of complex work and high pressure. The academic supervision model is important because it can help nurses manage workload, improve skills and knowledge, and reduce stress levels. Effective supervision is expected to improve the quality of health services, job satisfaction, and have a positive impact on patients and the health system as a whole. This study aims to determine the influence of academic model supervision on the workload and stress of nurses in hospitals. This study uses a literature review method from research articles in the Scopus and Google Scholar databases published in 2014-2023 with the keywords